2019
DOI: 10.1016/j.devcel.2019.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Dendritic Actin Network Formation in Extended Lamellipodia Drives Proliferation in Growth-Challenged Rac1P29S Melanoma Cells

Abstract: Highlights d Rac1 P29S confers proliferative advantage during melanoma metastasis and drug treatment d Rac1 P29S sustains proliferation in drug-challenged cells by elongation of lamellipodia d Rac1 P29S -driven proliferation needs matrix attachment but not focal adhesion signaling d Elongated lamellipodia in Rac1 P29S cells sequester and phospho-inactivate NF2/Merlin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 71 publications
(105 reference statements)
4
38
0
Order By: Relevance
“…S14). Recent work has suggested mechanistic links between enhanced branched actin formation in pseudopdial cell compartments and enhanced cell cycle progression (Mohan et al, 2019;Molinie et al, 2019), especially in micrometastases. Therefore, we lean towards an interpretation that connects the predicted metastatic efficiency under pseudopod formation to increased proliferation and survival.…”
Section: Interpretation Of Latent Features Discriminating High and Lomentioning
confidence: 99%
See 1 more Smart Citation
“…S14). Recent work has suggested mechanistic links between enhanced branched actin formation in pseudopdial cell compartments and enhanced cell cycle progression (Mohan et al, 2019;Molinie et al, 2019), especially in micrometastases. Therefore, we lean towards an interpretation that connects the predicted metastatic efficiency under pseudopod formation to increased proliferation and survival.…”
Section: Interpretation Of Latent Features Discriminating High and Lomentioning
confidence: 99%
“…Cells were then washed four times with 1X PBS and imaged at 20x magnification on a Nikon Eclipse Ti live cell microscope. Proliferation was quantified in these images using a point source detection algorithm described previously (Mohan et al, 2019).…”
Section: Measuring Extracellular Acidification Rate Oxygen Consumptimentioning
confidence: 99%
“…Consistently, the ectopic expression of RAC1 P29S in melanoma cell lines increases resistance to BRAF and MEK inhibitor therapies (Van Allen et al, 2014;Watson et al, 2014;Araiza-Olivera et al, 2018). Indeed, using a mouse xenograft model, the authors observed that this mutation enhances melanoma growth and invasion and confers drug resistance against BRAF and MEK kinase inhibitors (Revach et al, 2016;Mohan et al, 2019) (Table 1). More recently, using transgenic mouse models, it was also demonstrated that Rac1 P29S can cooperate with BRAF V600E to promote melanoma tumorigenesis (Lionarons et al, 2019).…”
Section: Rho Family Members Involved In Melanoma Migration and Invasionmentioning
confidence: 71%
“…Remarkably, the increased mitotic rate observed is due to the formation of lamellipodia, which are dependent on continuous actin polymerization and activate proliferative signaling cascades by inhibiting the neurofibromatosis type 2 (NF2)/Merlin tumor suppressor (Mohan et al, 2019). Consequently, NF2/Merlin inhibition by phosphorylation of the Rac effector PAK promotes melanoma cell resistance to MAPK inhibitors (Mohan et al, 2019) (Table 1). Consistently, the ectopic expression of RAC1 P29S in melanoma cell lines increases resistance to BRAF and MEK inhibitor therapies (Van Allen et al, 2014;Watson et al, 2014;Araiza-Olivera et al, 2018).…”
Section: Rho Family Members Involved In Melanoma Migration and Invasionmentioning
confidence: 99%
See 1 more Smart Citation